Dynamic neuroplasticity of language networks: The intersection of bilingualism and epilepsy - Alena Stasenko; Erik Kaestner; Adam J. Schadler; Anny Reyes; Clare Urbanic; Jonathan L. Helm; Daniel Saldana; Giselle Carollo-Duprey; Monika Połczyńska; Christopher Benjamin; Leigh N. Sepeta; Tamar H. Gollan; et al. (Proceedings of the National Academy of Sciences, 2025)
Are bilingual language networks flexible enough to dynamically adapt to neurological insult? We examined language lateralization in 24 bilingual and 46 monolingual adults with temporal lobe epilepsy using functional MRI. In a group of primarily early sequential bilingual patients, the first acquired language (L1) showed more bilateral lateralization than in monolingual patients, with no effect of seizure onset laterality. In contrast, the second-acquired language (L2) was more bilateral in the presence of left hemisphere epilepsy and more left-lateralized in right hemisphere epilepsy. Most notably, in left hemisphere epilepsy, seizure onset closer to L2 acquisition was associated with more right-lateralized L2 representation. These findings suggest a compensatory process in which L2 networks strengthen in the hemisphere opposite the seizure focus, potentially reflecting neural adaptation in early bilingualism. Conversely, L1 appears to have less dynamic reorganization in response to neurological insult. Together, these findings highlight the importance of timing in both language experience and neurological stress in shaping language network organization. They support the view that the bilingual brain is not simply the sum of two monolingual systems, but a dynamic and unique system marked by high interindividual variability, in which divergence between languages may emerge under certain experience- and context-dependent conditions.